A new approach for solving fractional differential-algebraic equations. Issue 6 (1st November 2017) - Ghomanjani, F.
Abstract: In this paper, the Bezier curves method is implemented to give approximate solutions for fractional differential-algebraic equations (FDAEs). This methods in applied mathematics can be used as approximated method for obtaining approximate solutions for different types of fractional differential equations. An illustrative example is included to demonstrate the validity and applicability of the suggested approach.